Lunch Lady and the field trip fiasco - Krosoczka, Jarrett (Krosoczka, Jarrett. Lunch Lady, 2011)
Lunch Lady, a secret crime fighter, accompanies the Breakfast Bunch on a class trip to an art museum, but when Dee, Hector, and Terrence begin to think there is something strange afoot, she suspects nothing.